MENSUKSESKAN MITIGASI BENCANA COVID-19: Analisis Kepercayaan Masyarakat pada Kebijakan Pemerintah Kota Samarinda - Apriani, Fajar; Saidi, Arbainah; Darmawan, Ady; Rahman, Ramadhan Aunur (Journal of Policy & Bureaucracy Management, 2021)
Local governments play an important role in disaster response, namely before, during and after the disaster. However, society has an attitude towards policies, which are formed the basis of the existence of trust values to further lead to self-acceptance of the policies carried out by the government. This study focuses on examining the important value of public trust in government policies in overcoming the Covid-19 pandemic in Samarinda City. This research is descriptive analythical using a mixed approach. Quantitative data collected through survey method, while qualitative data were collected from observation, documentation and literature study techniques. The population in this study were all residents of Samarinda City with a sample size of 193 respondents. Data were collected for two weeks using an online questionnaire that had been tested for reliability. Research result shows that the people of Samarinda City have good trust in government in mitigating the Covid-19 disaster as outlined in the health protocol implementation policy, Covid-19 vaccination and trust the seriousness of the government’s actions for the public. Public trust in various government actions in mitigating the Covid-19 disaster is one of the things that can affect the success of joint disaster management.